Principles of Distributed Systems 16th International Conference, OPODIS 2012, Rome, Italy, December 18-20, 2012. Proceedings - Baldoni, Roberto; Flocchini, Paola; Binoy, Ravindran; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the refereed proceedings of the 16th International Conference on Principles of Distributed Systems, OPODIS 2012, held in Rome, Italy, in December 2012. The 24 papers presented were carefully reviewed and selected from 89 submissions. The conference is an international forum for the exchange of state-of-the-art knowledge on distributed computing and systems. Papers were sought soliciting original research contributions to the theory, specification, design and implementation of distributed systems.
FixMe: A Self-organizing Isolated Anomaly Detection Architecture for Large Scale Distributed Systems -- Analyzing Global-EDF for Multiprocessor Scheduling of Parallel Tasks -- Range Queries in Non-blocking k-ary Search Trees -- On the Polling Problem for Social Networks -- Non-deterministic Population Protocols -- Stochastic Modeling of Dynamic Distributed Systems with Crash Recovery and Its Application to Atomic Registers -- When and How Process Groups Can Be Used to Reduce the Renaming Space -- Electing a Leader in Multi-hop Radio Networks -- Tree Exploration by a Swarm of Mobile Agents -- Crash Resilient and Pseudo-Stabilizing Atomic Registers -- Directed Graph Exploration -- Lattice Completion Algorithms for Distributed Computations -- Optimal Broadcast in Shared Spectrum Radio Networks -- Attack-Resilient Multitree Data Distribution Topologies -- On the Complexity of Distributed Broadcasting and MDS Construction in Radio Networks -- On the Impact of Identifiers on Local Decision -- Black Hole Search and Exploration in Unoriented Tori with Synchronous Scattered Finite Automata -- Algorithms for Partial Gathering of Mobile Agents in Asynchronous Rings -- Causality, Influence, and Computation in Possibly Disconnected Synchronous Dynamic Networks -- Wait-Free Stabilizing Dining Using Regular Registers -- Node Sampling Using Random Centrifugal Walks -- Physarum-Inspired Self-biased Walkers for Distributed Clustering -- Wait-Free Linked-Lists -- Replication.
Keywords: Computer science; Computer Communication Networks; Software engineering; Computer software; Computational complexity; Algebra -- Data processing; Artificial intelligence; Computer Science; Computer Communication Networks; Algorithm Analysis and Problem Complexity; Discrete Mathematics in Computer Science; Software Engineering; Artificial Intelligence (incl. Robotics).; Symbolic and Algebraic Manipulation